Private Information and the Monetary Model of Exchange Rates: Evidence from a Novel Data Set - Chinn, Menzie D.; Moore, Michael J. (My University, 2009)
The authors propose an exchange rate model that is a hybrid of the conventional specification with monetary fundamentals and the Evans-Lyons microstructure approach. They argue that the failure of the monetary model is principally due to private preference shocks that make the demand for money unstable. These shocks to liquidity preference are revealed through order flow. They estimate a model augmented with order flow variables, using a unique data set: almost 100 monthly observations on inter-dealer order flow on dollar/euro and dollar/yen. The augmented macroeconomic, or "hybrid," model exhibits out-of-sample forecasting improvement over the basic macroeconomic and random walk specifications.